Pentingnya Pendidikan Kewarganegaraan Dalam Membentuk Etika Sosial di Era Globalisasi - Marisa; Nursilah, Susi; Zebua, Wika Darismawati; Nufus, Azizatun; Hidayatullah, Muhammad Farhan (CV. Kurnia Grup, 2025)
Civic Education plays a central role in shaping the social ethics of young generations in the era of globalization. Globalization brings challenges in the form of massive information flows, foreign cultural influences, and changes in societal mindsets. This study employs adescriptive qualitative method through literature review to analyze the role of Civic Education in fostering social ethics based on the values of Pancasila. The findings show that Civic Education serves as a medium for character education, moral value cultivation, and the development of critical and responsible citizens. In conclusion, Civic Education must be developed through innovative, technology-based learning strategies to remain relevant to contemporary needs.